2022
DOI: 10.1002/jcu.23365
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound exploration of muscle characteristic changes and diabetic peripheral neuropathy in diabetic patients

Abstract: Purpose Using brightness mode ultrasound combined with shear wave elastography, this study aims to detect structural and functional changes of the medial head of gastrocnemius (MG) in type 2 diabetes mellitus (T2DM) patients with or without diabetic peripheral neuropathy (DPN). Methods 149 T2DM patients (DPN group and non‐DPN group) and 60 healthy volunteers (control group) were enrolled. We measured the absolute difference of fascicle length (FL), pennation angle (PA), and shear wave velocity (SWV) of both MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…While Harish et al [23] evaluated the alterations of Achilles tendon in type 2 diabetic patients and concluded that the patients had thicker tendons (P < 0.01) and lower mean shear wave velocity values (P < 0.001) compared to healthy volunteers, indicating tendon softening in diabetic patients. In a recent study [24], the medial head of the gastrocnemius (MG) of T2DM was measured for absolute differences in three parameters In addition, SWE can improve its diagnostic sensitivity and specificity when applied in combination with a clinical neurological scoring system and biochemical indicators to assess DPN. Wang et al [25] applied SWE in combination with the Toronto clinical scoring system to diagnose DPN.…”
Section: Application Of Swe In Diabetic Peripheral Neuropathymentioning
confidence: 99%
“…While Harish et al [23] evaluated the alterations of Achilles tendon in type 2 diabetic patients and concluded that the patients had thicker tendons (P < 0.01) and lower mean shear wave velocity values (P < 0.001) compared to healthy volunteers, indicating tendon softening in diabetic patients. In a recent study [24], the medial head of the gastrocnemius (MG) of T2DM was measured for absolute differences in three parameters In addition, SWE can improve its diagnostic sensitivity and specificity when applied in combination with a clinical neurological scoring system and biochemical indicators to assess DPN. Wang et al [25] applied SWE in combination with the Toronto clinical scoring system to diagnose DPN.…”
Section: Application Of Swe In Diabetic Peripheral Neuropathymentioning
confidence: 99%
“…For large muscle groups of lower extremities, Wang et al [ 19 ] discovered that diabetes duration over ten years and rectus femoris mass index (RFMI) lower than 2.2 cm 2 /m 2 were indicators of DPN with an accuracy of 0.75 (95% CI: 0.72–0.79, p < 0.001). Zhao et al [ 20 ] found that the muscle thickness and shear wave velocity of MG decreased among patients with DPN in the correlation analysis ( p < 0.01). However, no direct evidence showed the echo intensity of muscle performance among T2DM patients with and without DPN.…”
Section: Introductionmentioning
confidence: 99%